Cover Picture: A Facile Strategy for Selective Incorporation of Phosphoserine into Histones (Angew. Chem. Int. Ed. 22/2013). Issue 22 (2nd May 2013) - Lee, Sangsik; Oh, Seunghee; Yang, Aerin; Kim, Jihyo; Söll, Dieter; Lee, Daeyoup; Park, Hee‐Sung
<x xml:space="preserve">Abstract</x> Selective phosphoserine incorporation is described by H.‐S. Park et al. in their Communication on page 5771 ff. A general strategy for producing recombinant histones with site‐specific serine phosphorylation has been developed by engineering phosphoseryl‐tRNA synthethase (SepRS) and elongation factor Tu (EF‐Tu). This method should facilitate the study of histone phosphorylation and cross‐regulatory mechanisms.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>